miR-142-3p Regulates BDNF Expression in Activated Rodent Microglia Through Its Target CAMK2A - Gupta, Neelima; Jadhav, Shweta; Tan, Kai-Leng; Saw, Genevieve; Mallilankaraman, Karthik Babu; Dheen, S. Thameem (Frontiers in Cellular Neuroscience, 2020)
Microglia, the innate immune effector cells of the mammalian central nervous system (CNS), are involved in the development, homeostasis, and pathology of CNS. Microglia become activated in response to various insults and injuries and protect the CNS by phagocytosing the invading pathogens, dead neurons, and other cellular debris. Recent studies have demonstrated that the epigenetic mechanisms ensure the coordinated regulation of genes involved in microglial activation. In this study, we performed a microRNA (miRNA) microarray in activated primary microglia derived from rat pup’s brain and identified differentially expressed miRNAs targeting key genes involved in cell survival, apoptosis, and inflammatory responses. Interestingly, miR-142-3p, one of the highly up-regulated miRNAs in microglia upon lipopolysaccharide (LPS)-mediated activation, compared to untreated primary microglia cells was predicted to target Ca2+/calmodulin dependent kinase 2a (CAMK2A). Further, luciferase reporter assay confirmed that miR-142-3p targets the 3′UTR of Camk2a. CAMK2A has been implicated in regulating the expression of brain-derived neurotrophic factor (BDNF) and long-term potentiation (LTP), a cellular mechanism underlying memory and learning. Given this, this study further focused on understanding the miR-142-3p mediated regulation of the CAMK2A-BDNF pathway via Cyclic AMP-responsive element-binding protein (CREB) in activated microglia. The results revealed that CAMK2A was downregulated in activated microglia, suggesting an inverse relationship between miR-142-3p and Camk2a in activated microglia. Overexpression of miR-142-3p in microglia was found to decrease the expression of CAMK2A and subsequently BDNF through regulation of CREB phosphorylation. Functional analysis through shRNA-mediated stable knockdown of CAMK2A in microglia confirmed that the regulation of BDNF by miR-142-3p is via CAMK2A. Overall, this study provides a database of differentially expressed miRNAs in activated primary microglia and reveals that microglial miR-142-3p regulates the CAMK2A-CREB-BDNF pathway which is involved in synaptic plasticity.